Strategi Pemasaran Buah di UD. Wika Mitra Desa Kerobokan Kecamatan Kuta Utara - K. RATIH RAHAYUNINGSIH; I KETUT BUDI SUSRUS; A.A.A WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
ABSTRACT Fruit Marketing Strategy at UD. Wika Mitra Kerobokan Village, Kuta Utara This research is purpose to identify and to know internal environment (strengths and weaknesses) and external environment (opportunities and threats), business position, and marketing strategy as good enough to applied by UD.Wika Mitra based on currently position. The method of analysis used in this research is corporate environment which consists of IFE (Internal Factor Evaluation) matrix , EFE (External Factor Evaluation) matrix, and BCG (Boston Consulting Group) matrix. IFE matrix analysis with total score 2,50 and EFE matrix analysis with total score 3,020. BCG matrix analysis through the analysis of market growth rate and relative market share, known that in 2012 UD. Wika Mitra has market growth rate at 6,50% and the value of the relative market share at 1,18. Position UD. Wika Mitra is on the cell Cash Cow. This means the company has a small business opportunity because they are on the market that is not growing but it has a market share than main competitors UD. Setiawan. Based on the company's position, it can produce an alternative strategy that should be applied to the company, is a product development strategy and concentric diversification strategy. Keywords: marketing strategy, fruit, IFE, EFE, BCG